Proposta de metodologia para aplicação de eficiência energética em uma usina hidrelétrica - Bimestre, Thiago Averaldo [UNESP] (2015)
The energy efficiency projects play a key role in the improvement of energy security, environmental sustainability and economic performance. This research aims to present the development and results of a pilot project for energy efficiency applied to the hydroelectric power plant of Paraibuna. In this sense, a proposed methodology for optimization of energy use throughout the installation of a hydroelectric power plant was developed, looking, from inspection and testing results, analyze how electrical energy is being used and proposing improvements with regard to the rationalization of its application. In addition, the use of other existing energy sources and not exploited, as well as the application of new technologies, are evaluated, prioritizing the reduction of damage to the environment, reducing of maintenance costs and the increasing of economic gains. The actions of this project were aimed at rational energy use in lighting systems, air conditioning, pumping and heat exchangers responsible for the cooling of turbine bearings. Reductions achieved were significant, reaching 52% in the lighting system, 28% in the air conditioning system and 36% for pumping systems. About other energy sources, is presented a study on the implementation of photovoltaic systems connected to the network that result in a saving of 91.7 MWh/year. This work also presents a study on the use of the available hydraulic potential in a branch of the penstock of the plant with the implementation of a pelton turbine of 30 kVA. Finally, is evaluated the deployment of a small biodiesel plant, enough to feed the ferries which perform sailings on the dam. It is hoped that this study, expand research on energy efficiency by encouraging changes of habits, form features, updating and training the staff involved in the processes of production and use of energy and ... (Complete abstract click electronic access below)